Microstrip antenna design for use in 4G communication network systems - Ramadhon, M. Reza; Aribowo, Didik; Cahyono, Bagus Dwi (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
4G service coverage only reaches 52.90% of the total area in Indonesia, with an average internet speed of 11.12 Mbps which is one of the lowest internet speeds in Southeast Asia. The increasing need for internet also affects all aspects of life if internet services are still not optimal. This research was conducted with the aim of producing a microstrip antenna to be used as a supporting antenna to get better internet quality, as well as providing additional insight for the general public about the concept of microstrip antennas starting from planning, designing, testing, and using microstrip antennas. In this research, a microstrip antenna is made using the peripheral slits method, to work at frequencies of 1800-2400 MHz for 4G networks. microstrip antennas will pay attention and be analysed on the parameters of return loss (S-11), VSWR (Voltage Standing Wave Ratio), bandwidth, and antenna gain. simulation results for several parameters such as return loss which gets a value of -13.33639 dB and the VSWR value is obtained at 1.5489645 at a working frequency of 2311 MHz. The Gain magnitude obtained is 2.35 dBi and the antenna bandwidth value obtained is 30.6 MHz. These values have met the criteria of a good microstrip antenna and are ready to be fabricated and implemented which can be useful for improving the quality of public internet usage.